A method for regenerating composite positive electrode materials from retired lithium batteries

By dismantling and pretreating the retired lithium battery, graphene and composite positive electrode materials are prepared, which solves the problem of high purity requirements of raw materials in the prior art, and achieves efficient and environmentally friendly positive electrode materials for lithium battery.

CN115036605BActive Publication Date: 2025-04-15YUNNAN YUNTIANHUA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210728130.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-24
Publication Date
2025-04-15
Estimated Expiration
2042-06-24

AI Technical Summary

Technical Problem

In the prior art, the high requirements for raw materials in the process of recycled lithium battery positive electrode materials lead to high costs and poor applicability.

Method used

Graphene is prepared by dismantling and pretreatment of the decommissioned lithium battery, the negative electrode active material is recovered, and the positive electrode active material is mixed with the composite salt and calcined at low temperature. Then, the precipitation complexing agent and graphene are added to the aqueous solution for solvothermal reaction to prepare a high-performance carbon composite positive electrode material.

Benefits of technology

The process flow is simplified, the use of acid and alkali reagents is avoided, the electrochemical performance is improved, energy consumption and metal loss is reduced, the recovery rate is improved, and the green and efficient lithium battery recycling and treatment is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115036605B_ABST
    Figure CN115036605B_ABST
Patent Text Reader

Abstract

The invention discloses a method for regenerating composite positive electrode materials of retired lithium batteries, and relates to the technical field of lithium battery recycling and reuse. After pre-treatment, the graphite powder recovered from the negative electrode is prepared into high-performance graphene, and the lithium-containing powder recovered from the positive electrode is mixed with a composite salt, and reacted at low temperature to generate a water-soluble compound, and after water immersion and filtration, a precipitation complexing agent and the prepared graphene material are added to the filtrate, and a solvent thermal reaction is carried out under a certain molar ratio, temperature, time and pressure, and then filtered, washed and dried to obtain a composite carbon composite lithium battery positive electrode material. The introduction of chemical reagents such as acid and alkali is effectively avoided in the process, the operation is simple, the overall process flow is shortened, the electrochemical performance of the regenerated lithium ion battery positive electrode material is improved, and it has a reasonable energy intensity. It is a green and efficient new technology for recycling and processing retired lithium ion batteries, and has great prospects for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery recycling and reuse, and in particular to a method for regenerating composite positive electrode materials from retired lithium batteries. Background Art

[0002] Lithium-ion batteries (LIBs) have obvious advantages over traditional secondary power sources in terms of energy density, power density and life. Due to the rapid development of technology and the multiple effects of policy markets in the past decade, lithium-ion batteries have flourished in many fields. First, consumer electronics, followed by electric vehicles (EVs) and power grids, the global market share of lithium-ion batteries has skyrocketed. However, due to the limitations of operating life, more and more retired batteries are facing serious accumulation. Retired lithium batteries have serious safety hazards and environmental pollution. If not properly handled, they will inevitably have a negative impact on the ecological and social environment. At the same time, retired lithium batteries are enriched with a large amount of precious metal resources and the content is much higher than that of natural ores, such as cobalt and lithium. my country's import dependence exceeds 80%, which is an important strategic resource. Recycling of retired lithium batteries can absorb the hazards caused by retired lithium batteries, and at the same time provide raw materials for lithium battery production, alleviate the current situation of resource shortage, and ensure the sustainable development of my country's new energy industry.

[0003] Reasonable and efficient battery recycling technology is conducive to the sustainable development of lithium-ion batteries. The traditional recycling process of dissolving metals, separating and purifying to obtain high value-added products has to go through cumbersome steps, including acid-base leaching, filtration, solvent extraction, precipitation, etc., which not only increases the cost, but also causes serious secondary pollution to the atmospheric environment and water environment. At present, the development trend of retired lithium-ion battery recycling has gradually changed from optimizing traditional metallurgical processes to developing more diversified and green environmentally friendly methods. The sustainability of the recycling process has become an important evaluation factor. Direct regeneration is a closed-loop process that is completely different from traditional metallurgical processes. The whole process starts from one battery and ends with one battery, eliminating many separation and purification steps. However, the current direct regeneration of positive electrode materials has high requirements for the purity of raw materials. For example, patent CN110797602A repairs and regenerates positive electrode materials by directly replenishing lithium, but the raw materials used are only the powder obtained by post-processing of the failed pole pieces made of positive electrode materials, or the scraps of positive electrode materials. The materials are relatively pure and not widely used. Summary of the invention

[0004] The purpose of the present invention is to provide a method for regenerating composite positive electrode materials from retired lithium batteries, so as to solve the problem in the prior art that the raw materials used in the process of regenerating positive electrode materials of lithium batteries have high requirements, resulting in high cost and poor applicability.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solution: a method for regenerating composite positive electrode materials from retired lithium batteries, characterized in that it includes the following steps:

[0006] S1. Dismantle the waste lithium battery, remove the plastic shell, soak the electrode material in a solution and perform ultrasonic treatment, so that the electrolyte and the binder are dissolved in the solution, the positive electrode active material, the negative electrode active material and the conductive agent fall off from the aluminum foil and the copper foil, and then recover them according to their specific gravity, so that the positive electrode active material is a lithium-containing powder, and the negative electrode active material is a graphite powder; prepare the negative electrode active material graphite powder into graphene;

[0007] S2. The positive electrode active material containing lithium powder and the composite salt are mixed evenly, placed in a muffle furnace at a heating rate of 1 to 10 ° C / min from room temperature to 200 to 600 ° C, and kept warm for 0.1 to 6 hours for calcination;

[0008] S3. According to the solid-liquid ratio of 10 to 500 g / L, deionized water was added to the calcined product, stirred on a magnetic stirrer for 5 to 20 min, stirred until the solution was clear, and the solution was filtered to obtain a filtrate;

[0009] S4. Add a precipitating complexing agent to the filtrate and stir to form a mixed solution; add the graphene in step S1 to the mixed solution according to 0.1 to 4.5 wt% of the mass of the generated positive electrode material, disperse it evenly by ultrasonication for 30 to 60 min, transfer it to a polytetrafluoroethylene-lined stainless steel autoclave, and react at 150 to 400 ° C for 1 to 6 hours;

[0010] S5. After the reaction is completed and cooled to room temperature, the obtained precipitate is washed, filtered, and dried for 6 to 12 hours to obtain a high-performance carbon composite positive electrode material.

[0011] A further technical solution is that the positive electrode of the lithium battery is one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel cobalt oxide, lithium nickel manganese oxide, lithium cobalt manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide, and the negative electrode is a graphite negative electrode.

[0012] A further technical solution is that the composite salt is a mixture of one or more of chloride, phosphate, thiosulfate, pyrosulfate and persulfate, and the amount of the composite salt added is 1 to 10 times that of the lithium-containing powder.

[0013] A further technical solution is that in step S2, the lithium-containing powder and the composite salt are mixed by ball milling, the ball mill speed is 300-800 r / min, and the ball milling time is 1-6 h.

[0014] A further technical solution is that the precipitation complexing agent is at least one of urea, ammonium carbonate, acetamide, ammonium bicarbonate and acrylamide.

[0015] A further technical solution is that the ratio of the molar amount of the precipitation complexing agent to the total molar amount of metal ions in the solution is 5 to 15:1.

[0016] A further technical solution is that the carbon nanomaterial is one or a mixture of graphene, amorphous carbon spheres and carbon nanohorns.

[0017] A further technical solution is that the precipitate washing in step S5 is specifically performed by washing and filtering with water, ethanol or a mixed solution of the two until the conductivity is ≤120μs / cm and the pH is ≥3.

[0018] A further technical solution is that the solution in step S1 is at least one of propylene carbonate, acetonitrile and N-methylpyrrolidone.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention uses retired lithium batteries as raw materials, and after pre-treatment, the graphite powder recovered from the negative electrode is prepared into high-performance graphene, and the lithium-containing powder recovered from the positive electrode is mixed with a composite salt, and reacted at low temperature to generate a water-soluble compound, and after water immersion and filtration, a precipitation complexing agent and the prepared graphene material are added to the filtrate, and after a solvent thermal reaction at a certain molar ratio, temperature, time and pressure, the solvent is filtered, washed and dried to obtain a composite carbon composite lithium battery positive electrode material. The introduction of chemical reagents such as acid and alkali is effectively avoided in the process, the operation is simple, the overall process flow is shortened, the electrochemical performance of the regenerated lithium ion battery positive electrode material is improved, and it has a reasonable energy intensity. It is a green and efficient new technology for the recycling and treatment of retired lithium ion batteries, and has great prospects for industrial application. It improves the technical problems of large consumption of acid and alkali reagents, difficult waste liquid treatment, serious metal loss, high roasting temperature, high energy consumption, and low recovery rate in the current recycling process, as well as the quality problems of high impurity content and poor electrochemical performance of the recycled product. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a SEM image of the regenerated composite positive electrode material of a retired lithium battery prepared in Example 2.

[0022] Figure 2 This is a performance diagram of the retired lithium battery regenerated composite positive electrode material prepared in Example 1 at different rates.

[0023] Figure 3 This is a cycle performance diagram of the retired lithium battery recycled composite positive electrode material prepared in Example 1 at 1C rate. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0025] Example 1

[0026] A method for regenerating composite positive electrode materials from retired lithium batteries is as follows:

[0027] (1) Using undisassembled retired lithium iron phosphate battery cells as raw materials, dismantling the waste lithium batteries, removing the plastic shells, immersing the electrode materials in a solution (the solution is at least one of propylene carbonate, acetonitrile, and N-methylpyrrolidone) and ultrasonically treating them, so that the electrolyte and the binder are dissolved in the solution, and the positive electrode active material, the negative electrode active material and the conductive agent fall off from the aluminum foil and the copper foil. The copper foil and the aluminum foil are taken out, separated by specific gravity centrifugation, and recovered separately, and the positive electrode active material is a lithium-containing powder, and the negative electrode active material is a graphite powder and a conductive agent.

[0028] (2) The negative electrode active material graphite powder is prepared into graphene. The preparation method refers to patent CN108046249A "A method for preparing graphene".

[0029] (3) The positive electrode active material lithium iron phosphate (containing lithium powder) obtained by pretreatment was mixed with ammonium dihydrogen phosphate in a mass ratio of 1:2 and placed in a muffle furnace at 5°C min -1 The heating rate was from room temperature to 200 °C and kept for 4 h. The solid-liquid ratio was 100 g·L -1 , add a certain amount of deionized water to the calcined product, stir on a magnetic stirrer for 5 minutes, stir until the solution is clear, filter the solution to obtain a filtrate, add precipitating complexing agent urea to the filtrate, and stir evenly to form a mixed solution.

[0030] (3) The prepared graphene material was added to the mixed solution at 4.5wt% of the mass of the final positive electrode material, and ultrasonicated for 30 minutes, and then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and reacted at 180°C for 240 minutes. After the reaction was completed and cooled to room temperature, the obtained precipitate was washed several times with deionized water and ethanol, and dried in a vacuum drying oven at 80°C for 12 hours to obtain a high-performance carbon composite positive electrode material LFP@GO.

[0031] The composite carbon composite positive electrode material LFP@GO was ground and mixed with PVDF and conductive carbon black in a mass ratio of 8:1:1 in an open air atmosphere (humidity 60%, temperature 26°C), and then NMP solvent was added to continue grinding until a viscous and uniform slurry was formed. The slurry was evenly coated on a clean aluminum foil, pre-dried at 80°C for 0.5h in a coater, and then placed in a vacuum drying oven for further drying, maintaining 80°C for 12h, and finally a positive electrode sheet with an area of ​​1.33cm2 was prepared by a punching machine to obtain a positive electrode sheet for a button battery. The process was carried out in a glove box filled with high-purity argon gas, with a metal lithium sheet as the negative electrode, Teklon's UH20140 diaphragm, and 1mol / L LiPF6 / EC+DMC+EMC (the volume ratio of the three is 1:1:1) solution as the electrolyte to assemble a CR2025 button-type simulation battery; the electrochemical properties were tested at 30°C using a Xinwei battery testing system. The charge and discharge cycle performance test was carried out at room temperature at a rate of 1C using the Xinwei battery test system. The charge and discharge rate performance test was carried out at different rates (0.1C-0.2C-0.5C-1C-2C-5C-10C). The result curves are as follows: Figure 2 and Figure 3 As shown, the discharge capacity at 1C is 152 mAh / g, and the discharge capacity at 10C is 116 mAh / g, and the electrical performance is comparable to that of commercial materials.

[0032] Example 2

[0033] A method for regenerating composite positive electrode materials from retired lithium batteries is as follows:

[0034] (1) The steps of crushing, disassembling and sorting retired lithium battery cells are the same as those in Example 1, and the recovered graphite powder is prepared into graphene material.

[0035] (2) The recovered positive electrode active material, lithium nickel cobalt aluminum oxide, was mixed evenly with NH4Cl powder in a mass ratio of 1:3.5 and placed in a muffle furnace at 3°C ​​min -1 The heating rate was from room temperature to 400℃ and kept for 5h. -1 solid-liquid ratio, add deionized water, stir on a magnetic stirrer for 15 minutes, stir until the solution is clear, filter the solution to obtain a filtrate, add precipitating complexing agent ammonium carbonate to the filtrate, stir evenly to form a mixed solution.

[0036] (3) Add the prepared graphene material according to 2.0wt% of the mass of the generated positive electrode material into the mixed solution and ultrasonicate for 45min, transfer it to a polytetrafluoroethylene-lined stainless steel autoclave, and react at 400℃ for 180min. After the reaction is completed and cooled to room temperature, wash and dry it in the same way as in Example 1 to obtain a high-performance carbon composite positive electrode material LiNiCoAlO2@GO. Its SEM image is as follows Figure 1 As shown, graphene is uniformly attached around the positive electrode material.

[0037] Example 3

[0038] A method for regenerating composite positive electrode materials from retired lithium batteries is as follows:

[0039] (1) The steps of crushing, disassembling and sorting retired lithium battery cells are the same as those in Example 1, and the recovered graphite powder is prepared into graphene material.

[0040] (2) The recovered positive electrode active material lithium manganese oxide and sodium pyrosulfate were mixed uniformly in a mass ratio of 1:1 and placed in a muffle furnace at 10°C min -1 The heating rate was from room temperature to 550℃ and kept at this temperature for 30min. -1 Solid-liquid ratio, add deionized water, stir on a magnetic stirrer for 10 minutes until the solution is clear, filter the solution to obtain a filtrate, add precipitating complexing agent acrylamide to the filtrate, stir evenly to form a mixed solution.

[0041] (3) The prepared graphene material was added to the mixed solution at 0.5 wt% of the mass of the generated positive electrode material, and ultrasonicated for 60 min, and then transferred to a polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 150° C. for 120 min. After the reaction was completed and cooled to room temperature, the mixture was cleaned and dried as in Example 1 to obtain a high-performance carbon composite positive electrode material LiMn2O4@CNH.

[0042] Example 4

[0043] A method for regenerating composite positive electrode materials from retired lithium batteries is as follows:

[0044] (1) The steps of crushing, disassembling and sorting retired lithium battery cells are the same as those in Example 1, and the recovered graphite powder is prepared into graphene material.

[0045] (2) The recovered positive electrode active material lithium cobalt oxide and Na2S2O3 were mixed evenly in a mass ratio of 1:10 and placed in a muffle furnace at 5°C min -1 The heating rate was from room temperature to 300℃ and kept for 2h; according to 200g·L -1 solid-liquid ratio, add deionized water, stir on a magnetic stirrer for 20 minutes, stir until the solution is clear, filter the solution to obtain a filtrate, add precipitating complexing agent ammonium bicarbonate to the filtrate, and stir evenly to form a mixed solution.

[0046] (3) The prepared multilayer graphene carbon nanomaterial was added to the mixed solution at 0.1wt% of the mass of the generated positive electrode material, and ultrasonicated for 15min, and then transferred to a polytetrafluoroethylene-lined stainless steel autoclave, and reacted at 250°C for 60min. After the reaction was completed and cooled to room temperature, the mixture was cleaned and dried as in Example 1 to obtain a high-performance carbon composite positive electrode material LiCoO2@GO.

[0047] Although the present invention is described herein with reference to a number of illustrative embodiments of the present invention, it will be appreciated that those skilled in the art may devise many other modifications and implementations that fall within the scope and spirit of the principles disclosed herein. More specifically, within the scope of the present disclosure, drawings, and claims, a variety of variations and modifications may be made to the components or layout of the subject combination layout. In addition to variations and modifications made to the components or layout, other uses will also be apparent to those skilled in the art.

Claims

1. A method for regenerating composite positive electrode materials from retired lithium batteries, characterized in that The steps include: S1. Dismantle the waste lithium battery, remove the plastic shell, soak the electrode material in a solution and perform ultrasonic treatment, so that the electrolyte and the binder are dissolved in the solution, the positive electrode active material, the negative electrode active material and the conductive agent fall off from the aluminum foil and the copper foil, and then recover them according to their specific gravity, so that the positive electrode active material is a lithium-containing powder, and the negative electrode active material is a graphite powder; prepare the negative electrode active material graphite powder into graphene; S2. The positive electrode active material containing lithium powder and the composite salt are mixed uniformly, placed in a muffle furnace at a heating rate of 1 to 10 ° C / min from room temperature to 200 to 600 ° C, and kept warm for 0.1 to 6 hours for calcination; the composite salt is one of ammonium dihydrogen phosphate, ammonium chloride, sodium pyrosulfate and sodium thiosulfate; S3. According to the solid-liquid ratio of 10 to 500 g / L, deionized water was added to the calcined product, stirred on a magnetic stirrer for 5 to 20 min, stirred until the solution was clear, and the solution was filtered to obtain a filtrate; S4. Add a precipitating complexing agent to the filtrate and stir to form a mixed solution; add the graphene in step S1 to the mixed solution according to 0.1 to 4.5 wt% of the mass of the generated positive electrode material, disperse it evenly by ultrasonication for 30 to 60 min, transfer it to a polytetrafluoroethylene-lined stainless steel autoclave, and react at 150 to 400 ° C for 1 to 6 hours; S5. After the reaction is completed and cooled to room temperature, the obtained precipitate is washed, filtered, and dried for 6 to 12 hours to obtain a high-performance carbon composite positive electrode material.

2. The method for regenerating composite positive electrode materials from retired lithium batteries according to claim 1, characterized in that: The positive electrode of the lithium battery is one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel cobalt oxide, lithium nickel manganese oxide, lithium cobalt manganese oxide, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide, and the negative electrode is a graphite negative electrode.

3. The method for regenerating composite positive electrode materials from retired lithium batteries according to claim 1, characterized in that: The amount of the composite salt added is 1 to 10 times that of the lithium-containing powder.

4. The method for regenerating composite positive electrode materials from retired lithium batteries according to claim 1, characterized in that: In step S2, the lithium-containing powder and the composite salt are mixed by ball milling, the speed of the ball mill is 300-800 r / min, and the ball milling time is 1-6 hours.

5. The method for regenerating composite positive electrode materials from retired lithium batteries according to claim 1, characterized in that: The precipitation complexing agent is at least one of urea, ammonium carbonate, acetamide, ammonium bicarbonate and acrylamide.

6. The method for regenerating composite positive electrode materials from retired lithium batteries according to claim 5, characterized in that: The ratio of the molar amount of the precipitation complexing agent to the total molar amount of metal ions in the solution is 5 to 15:

1.

7. The method for regenerating composite positive electrode materials from retired lithium batteries according to claim 1, characterized in that: The precipitate washing in step S5 is specifically performed by washing and filtering with water, ethanol or a mixed solution of the two until the conductivity is ≤120 μs / cm and the pH is ≥3.

8. The method for regenerating composite positive electrode materials from retired lithium batteries according to claim 1, characterized in that: The solution in step S1 is at least one of propylene carbonate, acetonitrile, and N-methylpyrrolidone.

Citation Information

Patent Citations

  • Preparing method of graphene

    CN108046249A

  • METHOD OF PREPARING CARBON-COATED CATHODE ACTIVE MATERIAL BASED ON XLi2MNO3-(1-X)LiMO2 (M IS TRANSITION METAL SUCH AS NI, CO, OR MN) FOR LITHIUM SECONDARY BATTERY

    US20220328841A1